Dynamics of Baltic Sea phages driven by environmental changes. (7th July 2021) - Hoetzinger, Matthias; Nilsson, Emelie; Arabi, Rahaf; Osbeck, Christofer M. G.; Pontiller, Benjamin; Hutinet, Geoffrey; Bayfield, Oliver W.; Traving, Sachia; Kisand, Veljo; Lundin, Daniel; Pinhassi, Jarone; Middelboe, Mathias; et al.
Summary: Phage predation constitutes a major mortality factor for bacteria in aquatic ecosystems, and thus, directly impacts nutrient cycling and microbial community dynamics. Yet, the population dynamics of specific phages across time scales from days to months remain largely unexplored, which limits our understanding of their influence on microbial succession. To investigate temporal changes in diversity and abundance of phages infecting particular host strains, we isolated 121 phage strains that infected three bacterial hosts during a Baltic Sea mesocosm experiment. Genome analysis revealed a novel Flavobacterium phage genus harboring gene sets putatively coding for synthesis of modified nucleotides and glycosylation of bacterial cell surface components. Another novel phage genus revealed a microdiversity of phage species that was largely maintained during the experiment and across mesocosms amended with different nutrients. In contrast to the newly described Flavobacterium phages, phages isolated from a Rheinheimera strain were highly similar to previously isolated genotypes, pointing to genomic consistency in this population. In the mesocosm experiment, the investigated phages were mainly detected after a phytoplankton bloom peak. This concurred with recurrent detection of the phages in the Baltic Proper during summer months, suggesting an influence on the succession of heterotrophic bacteria associated with phytoplankton blooms.